TP53 and Beta-catenin mutations in liver tumours - Hainaut, Pierre (Iatreia, 2007)
HBV and HCV play key roles in the etiopathogenesis of Hepatocellular carcinoma (HCC) . Studies mostly based on cases from Western countries suggest distinct genetic pathways of carcinogenesis involving either TP53 or CTTNB1 mutations. Inappropriate reactivation of Wnt pathway due to mutations in CTNNB1 (Beta-Catenin) gene itself is also frequently reported. Mutant Beta-catenin escapes to ubiquitination and down regulation by GSK3-B, it accumulates and trans-activates variety of oncogenes involved in neoplasmic transformation mimicking Wnt pathway activation. Taking into consideration viral infection, chromosome instability and TP53 /Beta-catenin alterations, Laurent-Puig et al. described two distinct HCC profiles in a serie of 137 HCC cases , the first one associates HBV infection with frequent chromosomal alteration and distributes with TP53 mutations, the second would be observed in HBV negative large sized tumors and distributes with Beta-catenin mutations. We have investigated the status of HBV and HCV infections and of genetic alterations in TP53 and CTTNB1 in 26 patients with HCC from Thailand. In tumours, HBV DNA was found in 19 cases (73%) and HCV RNA in 4 cases (15.4% cases), 3 of whom were co-infected. Among the 19 HBV positive cases, sequencing of S gene showed genotype C in 82% and genotype B in 18%. Furthermore, 5/19 cases were negative for HBsAg and were categorized as occult HBV infections. TP53 mutations were detected in 9 cases (34,6%) including 7 mutations at codon 249 (AGG to AGT, arginine to serine), considered as ";fingerprint"; of mutagenesis by aflatoxin metabolites. All cases with 249ser mutation had overt HBV infection. CTNNB1 mutations were found in 6/26 cases (23%), 4 of whom also had TP53 mutation. There was no significant association between CTTNB1 mutations and viral infection status. These results suggest that mutagenesis by aflatoxin may have an impact greater than recognized sofar in the etiopathogenesis of HCC in Thailand. Furthermore, TP53 and CTNNB1 mutations do not appear as mutually exclusive, and TP53 249ser mutation is associated with overt HBV infection. Thus, HCC in this context may develop according to a sequence of genetic events that includes both TP53 and CTNNB1 mutations.